Studies of Nondefective Adenovirus 2-Simian Virus 40 Hybrid Viruses VIII. Association of Simian Virus 40 Transplantation Antigen with a Specific Region of the Early Viral Genome - Lewis, Andrew M. (1973)
Two of the five nondefective adenovirus 2 (Ad2)-simian virus 40 (SV40) hybrids induce SV40 transplantation resistance in immunized hamsters. These two hybrids, Ad2(+)ND(2) and Ad2(+)ND(4), contain 32 and 43% of the SV40 genome, respectively. The pattern of induction of SV40 transplantation antigen (TSTA) by the various hybrids differentiates TSTA from both SV40 U and T antigens. Since the SV40 RNA induced by both these hybrids is early SV40 RNA, these findings confirm that TSTA is an early SV40 function. By combining available data on SV40 antigen induction by these hybrids with electron microscopy heteroduplex mapping studies, the DNA segment responsible for the induction of SV40 TSTA can be inferred to lie in the region between 0.17 and 0.43 SV40 units from the site on the SV40 chromosome cleaved by E. coli R(1) restriction endonuclease.